Konstruksi Karakter Religius Siswa Melalui Kegiatan Keagamaan di Sekolah Dasar Negeri Kelayan Dalam 5 Banjarmasin Selatan - Nur Halijah Halijah (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2024)
Education serves as a crucial medium for nurturing students, and the humanistic achievements of education subsequently become a foundation for development. Therefore, it is expected that educators refrain from making educational errors while fulfilling their responsibilities. Character education, in this context, is the type of education that fosters the social, emotional, and moral growth of students. Consequently, character education is vital for shaping students' personalities and is anticipated to serve as a primary foundation for developing religious individuals who are prepared to compete in the future. This research aims to illustrate the construction of students' religious character through religious activities at the State Elementary School of Kelayan Dalam 5 in Banjarmasin City. The focus of this study includes: the concepts, implementation, and impacts of religious activities on students' religious character. This research employs a descriptive qualitative approach with data collection techniques that encompass observation, interviews, and documentation. The subjects of the study consist of the school principal, Islamic education teachers, and students. The findings indicate that the formation of religious character is integrated into the school's vision and mission, as well as in the learning programs and routine activities such as congregational prayers, recitation of short surahs, and extracurricular activities with a religious theme. The implications of this implementation are evident in the enhancement of students' religious morals, understanding of worship, and the development of discipline and courtesy